2017
DOI: 10.1038/s41598-017-04871-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-glacial biogeography of trembling aspen inferred from habitat models and genetic variance in quantitative traits

Abstract: Using species distribution models and information on genetic structure and within-population variance observed in a series of common garden trials, we reconstructed a historical biogeography of trembling aspen in North America. We used an ensemble classifier modelling approach (RandomForest) to reconstruct palaeoclimatic habitat for the periods 21,000, 14,000, 11,000 and 6,000 years before present. Genetic structure and diversity in quantitative traits was evaluated in common garden trials with 43 aspen collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
(63 reference statements)
2
20
0
Order By: Relevance
“…Consistent with initial expectations, ENM hindcasting provided geospatial evidence for trailing‐edge dynamics overall and especially within cluster 3 (Figures 6 and Figure ). Indeed, the inferred contraction of cluster 3 to a mid‐continental glacial refugium matches well with previous LGM–recent ENM hindcasting results (Ding et al, 2017) and paleobotanical records of Populus species shifting to cool mixed boreal and nonanalog forests in the same area ~18 ka during the LGM and subsequently expanding northward to higher temperate latitudes with other tree species (e.g., Alnus and Abies pollen types; Jackson et al, 2000; Williams et al, 2004; Breen et al , 2012). However, contradicting expectations based on these studies, previous genetic results (Callahan et al, 2013), and theoretical predictions that populations near refugial locations should harbor greater genetic diversity (Excoffier et al, 2009; Hewitt, 1996, 2001), we failed to recover clear genetic imprints of northward postglacial range expansion for P. tremuloides as a whole and for cluster 3 (Figure 4 and Figure ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with initial expectations, ENM hindcasting provided geospatial evidence for trailing‐edge dynamics overall and especially within cluster 3 (Figures 6 and Figure ). Indeed, the inferred contraction of cluster 3 to a mid‐continental glacial refugium matches well with previous LGM–recent ENM hindcasting results (Ding et al, 2017) and paleobotanical records of Populus species shifting to cool mixed boreal and nonanalog forests in the same area ~18 ka during the LGM and subsequently expanding northward to higher temperate latitudes with other tree species (e.g., Alnus and Abies pollen types; Jackson et al, 2000; Williams et al, 2004; Breen et al , 2012). However, contradicting expectations based on these studies, previous genetic results (Callahan et al, 2013), and theoretical predictions that populations near refugial locations should harbor greater genetic diversity (Excoffier et al, 2009; Hewitt, 1996, 2001), we failed to recover clear genetic imprints of northward postglacial range expansion for P. tremuloides as a whole and for cluster 3 (Figure 4 and Figure ).…”
Section: Discussionsupporting
confidence: 90%
“…Several important gaps in our knowledge of P. tremuloides evolutionary history remain open to investigation, including whether additional data from high‐throughput sequencing might confirm or refine previously described intraspecific genetic clusters (Callahan et al, 2013), and the nature of Pleistocene range dynamics [e.g., refugia since the Last Interglacial (LIG), but see Ding, Schreiber, Roberts, Hamann, and Brouard (2017)] and their influence on intraspecific genetic variation. To address these knowledge gaps, we investigate the genetic structure and population history of P. tremuloides by integrating phylogeographical analyses of genotyping‐by‐sequencing (GBS) data (Elshire et al, 2011) with ecological niche modeling (ENM; Peterson et al, 2011) analyses predicting the species Pleistocene to recent geographical range dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The work presented here constitutes the first complete, or baseline, survey of plant species at the iconic Pando aspen clone in central Utah, USA. The massive Pando aspen clone has likely survived for millennia [41], though as a result of recent human actions there are clearly at least three distinct plant communities supported under a genetically uniform forest canopy (Table 1). Our results also indicate distinct plant communities, interestingly, within separate fenced exclosures at Pando.…”
Section: Group and Species Preferences In A Single-genotype Forestmentioning
confidence: 99%
“…These integrated genetic and ENM results agree with other studies of Pacific Northwestern plants that found reductions of genetic diversity during northward post-glacial expansions in perennials and conifers (reviewed by Soltis et al 1997;Jaramillo-Correa et al 2009). The inferred contraction of cluster 3 to a mid-continental glacial refugium likewise matches well with previous LGM-recent ENM hindcasting results (Ding et al 2017) and paleobotanical records of Populus species shifting to cool mixed boreal and non-analog forests in the same area ∼18 ka during the LGM and subsequently expanding northward to higher temperate latitudes with other arboreal species (e.g. Alnus and Abies pollen types; Jackson et al 2000;Williams et al 2004;Breen et al 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Several important gaps in our knowledge of P. tremuloides evolutionary history remain open to investigation, including whether additional data from high-throughput sequencing might confirm or refine previously described intraspecific genetic clusters (Callahan et al 2013), and the nature of Pleistocene range dynamics [e.g. refugia since the Last Interglacial (LIG); but see Ding et al (2017)] and their influence on intraspecific genetic variation. To address these knowledge gaps, we investigate the genetic structure and population history of P. tremuloides by integrating phylogeographical analyses of genotyping-by-sequencing (GBS) data (Elshire et al 2011) with ecological niche modeling (ENM; Peterson et al 2011) analyses predicting the species Pleistocene to recent geographical range-dynamics.…”
Section: Introductionmentioning
confidence: 99%